Internalization of Religious Values in The Islam Program Teacher's Family Education of High School and High Vocational School Muhammadiyah Banjarmasin - Abd. Basir; Abdul Rahman (Nazhruna: Jurnal Pendidikan Islam, 2020)
Technology that develops along with social changes so that it has an impact on human life, including educational institutions in the family. The study in this study is a field with a phenomenological nature. This study aims to examine the PAI high school and vocational high school Muhammadiyah teachers in Banjarmasin City about the values given by parents as religious teachers to their children. The results showed that; First, the values given by parents as PAI teachers in Banjarmasin City in providing education in the family are to give the values of faith, faith and sharia. Second, the challenges are so great for parents as teachers in providing education to their children, so parents provide additional religious education to their children, which is to enter the boarding school with a full day school learning system.